POSTNATAL MOTHERS’ EXPERIENCE OF DOMESTIC VIOLENCE AGAINST WOMEN DURING PREGNANCY - Kumari Acharya, Tara; Bhattarai, Sanju; Adhikari, Bijaya; Ghimire, Ambika; Bajracharya, Karuna (Journal of Chitwan Medical College, 2024)
Background: Violence against women is a social problem that has serious consequences on women’s physical, and psychosocial well-being. The violence against women ultimately also affects children, families, and society as a whole. This study aimed to identify the experience of domestic violence against women during pregnancy. Methods: A descriptive cross-sectional study was conducted among purposively selected 302 postnatal mothers of postpartum A, B and Gynae ward of Patan Hospital. Data were collected through face-to-face interviews using a structured interview schedule. Data were analyzed in IBM SPSS Statistics version 20.0 using descriptive statistics. Results: Postnatal mothers experienced sexual violence by their husbands (8.9%), physical violence (12.9%), and emotional violence (43%) from their husbands and or family members. Regarding other forms of violence, mothers experienced not being given nutritious food during pregnancy (38.4%) and violence by their mother-in-law (45.4%). Likewise, few number of mothers have reported the violence (17.2%). Among them, 76.9% reported the incident of violence to the maternal side. Conclusions: The findings suggest a concerning prevalence of various forms of violence against postnatal mothers like sexual, physical, and emotional. Among those form of violence, existence of emotional violence was high and often perpetrated by husbands or family members. Moreover, the low reporting rates highlight the urgent need for enhanced support structures and interventions to empower victims and address the underlying issues contributing to this pervasive problem.